Pengaruh Peningkatan Berat Badan Selama Kehamilan Terhadap Berat Badan Bayi Baru Lahir Di Puskesmas Kediri Tahun 2016 - Aryani, Ni Putu; Annisa, Nurul Hikmah (Bunda Edu-Midwifery Journal (BEMJ), 2019)
Birthweight is influenced by internal and external factors. This study aims to identify the effect of weight gain during pregnancy on birth weight. The study design used a descriptive correlation with a total sample of 100 people using a total sampling method. The study was conducted at the Kediri Community Health Center in April 2016. The results showed that there was a significant relationship between weight gain during pregnancy and birth weight. It is expected that health workers can work together to further enhance counseling, especially regarding the health of pregnant women.